The Relationship Between Optimism and Anxiety Before the TNI-Polri Test: Hubungan Antara Optimisme dengan Kecemasan Menjelang Tes TNI-Polri - Cahyani, Nikita Bella Olivia Regita; Maryam, Effy Wardati (Indonesian Journal of Innovation Studies, 2023)
This research was motivated by the phenomenon of students experiencing anxiety before the TNI-Polri test. Characterized by fear or individual appearance, the feeling that something bad is about to happen. This study aims to determine the relationship between Optimism and Anxiety before the TNI-Polri test on the TNI-Polri tutoring students. This research is a type of correlational quantitative research. The variables in this study were optimism as the independent variable and anxiety as the dependent variable. This research was conducted at the TNI-Polri tutoring center with a sample of 60 students from the entire population, which were taken using the saturated sampling technique. The data collection technique used two Likert model psychological scales, namely the optimism scale and the scale before the TNI-Polri test. Analysis of the data used is Pearson Product Moment correlation with the help of SPSS 18 for windows. The result of the correlation coefficient is -0.396 with a significance of 0.002. Which implies a negative relationship between optimism and anxiety ahead of the TNI-Polri. The effective contribution of optimism with anxiety ahead of the TNI-Polri test is 15.7%.